Study on the Prosthesis Structural Design and Vibration Characteristics Based on the Conduction Effect of Human Middle Ear. (21st May 2020) - Ren, Wu; Yan, Huijuan; Yu, Yi; Ren, Jinghong; Chang, Jinlong; Wang, Yidong; Han, Yibo
Abstract : As a bridge from the sound signal in the air to the sound perception of the inner ear auditory receptor, the tympanic membrane and ossicular chain of the middle ear transform the sound signal in the outer ear through two gas-solid and solid-liquid conversions. In addition, through the lever principle formed by three auditory ossicle structure, the sound was concentrated and amplified to the inner ear. However, the sound transmission function of the middle ear will be decreased by disease, genetic, or trauma. Hence, using middle ear prosthesis to replace the damaged ossicles can restore the conduction function. The function realization of middle ear prosthesis depends on the vibration response of the prosthesis from the tympanic membrane to the stapes plate on the human auditory perception frequency, which is affected by the way the prosthesis combined with the tympanic membrane, the material, and the geometric shape. In this study, reasonable prosthetic structures had been designed for different types of ossicular chain injuries, and the frequency response characteristics were analyzed by the finite element method then. Moreover, in order to achieve better vibration frequency response, a ball structure was designed in the prosthesis to simulate its amplification function. The results showed that the middle ear prostheses constructed by different injury types can effectively transfer vibration energy. In particular, the first- and second-order resonant frequencies and response amplitudes are close to each other when ball structure models of different materials are added. Instead, the resonance frequency of the third stage formed by aluminum alloy ball materials is larger than that of the other two, which showed good response features.